Development of Student Worksheets Based on Etno-STEM on Sound Waves - Sari, Sri Wahyuni Juyka; Palittin, Ivylentine D; Henukh, Anderias (Kasuari: Physics Education Journal (KPEJ), 2023)
The purpose of this study was to determine the feasibility and legibility of the Ethno-STEM LKPD based on sound wave material. The research method used is Research and Development (R&D) with a 4D development model (Define, Design, Development, Disseminate) which is limited to three stages, namely define, design and development. The subjects in this study were students of class XI in several schools in Merauke, totaling 35 students. The result of this research is LKPD based on Ethno-STEM sound wave material. The results of material expert validation are 111.5 in the very appropriate category, media expert validation is 88 in the appropriate category, and the results of the readability test are 87% in the very feasible category. So it can be concluded that the Ethno-STEM-based LKPD on sound wave material is very suitable for use in the physics learning process of sound wave material.